Kekuatan Pemasaran Digital: Analisis Dampak Iklan, Celebrity Endorsement, Dan Influencer Marketing Terhadap Niat Beli Konsumen - Charis, Jessica Caroline; Rotty, Geraldo Valentino; Wiraputra, Ardina Lukita; Parani, Rizaldi (CV. ITTC INDONESIA, 2023)
This study examines the effects of various digital marketing strategies, including social media advertising, celebrity endorsements, and influencer marketing, on consumer purchase intentions within the Indonesian cosmetics industry, with a specific focus on the Scarlett cosmetics brand. In the ever-evolving digital landscape characterized by intense competition, understanding the most effective marketing techniques deployed on social media platforms is crucial. The study employs a qualitative research methodology, utilizing a case study framework with three informants as the primary subjects. In-depth interviews were conducted, guided by research objectives and contextual background. The interviews were recorded, transcribed, and analyzed qualitatively to identify patterns, themes, and perspectives emerging from the informants' insights. The findings provide valuable insights into the effectiveness of each digital marketing tactic in influencing consumer purchase intentions. Notably, this qualitative methodology facilitates a deeper understanding of how digital marketing tactics impact real-world consumer intentions. The informants' practical insights shed light on the underlying meanings and contexts of the research outcomes. This study serves as a foundation for organizations seeking to select the most suitable digital marketing methods to enhance consumer purchase intentions, particularly on the Instagram platform. It is essential to acknowledge the limitations of this research, primarily its exclusive focus on the cosmetics industry in Indonesia. Future research initiatives should aim to explore variations across different social media platforms and expand the geographical scope to achieve a more comprehensive comprehension of the subject matter.